PENGEMBANGAN E-BOOK BAHASA INDONESIA MENGGUNAKAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION PADA MATERI MEMBACA PEMAHAMAN DI KELAS IV SEKOLAH DASAR - Ismayanti; Muhammadi; Elfia Sukma; Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low reading comprehension ability of fourth-grade elementary school students and the suboptimal use of digital learning media, even though technological facilities such as projectors and internet networks are available at school. Learning is still dominated by conventional methods so that students are less active and experience difficulties in understanding the content of the reading, finding the main idea, and drawing conclusions. This study aims to develop an Indonesian e-book using the Cooperative Integrated Reading and Composition (CIRC) model on reading comprehension material in fourth-grade elementary schools that is valid, practical, and effective. This type of research is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fourth-grade students in three elementary schools. Data collection techniques were carried out through validation sheets, practicality questionnaires, and pre-tests and post-tests. The results showed that the developed E-Book had a validity level of 94.25% with a very valid category. The practicality of the E-Book was categorized as very practical, with teacher responses of 95.83% and 97.91%, respectively, and student responses ranging from 94.34% to 96.42%. The effectiveness of the E-Book was demonstrated by the improvement in student learning outcomes, with N-Gain values ​​of 81.61%, 92.56%, and 84.58% in the effective category. Thus, the Indonesian E-Book based on the CIRC model is feasible, practical, and effective for improving the reading comprehension skills of fourth-grade elementary school students.